2009
DOI: 10.1080/01446190903171196
|View full text |Cite
|
Sign up to set email alerts
|

A framework of critical resource chain for project schedule analysis

Abstract: To analyze a schedule is beneficial to understand and organize a project. Project schedules, in which time plans are created based on the Critical Path Method (CPM) or on Resource-Constrained Project Scheduling Problem (RCPSP) optimization, are targets herein. According to the concepts of the Theory of Constraints (TOC), a schedule is treated as a system. Schedule elements are suspected constraints. Moreover, a goal depends on the policy of schedule creation. Schedules are further analyzed herein to recognize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…21,31,32 Pellicer 33 reported that both the standardization of a control management process and the implementation of "best practice" project control enhance the effectiveness of PCS by reducing the effort required to collect and enter data and produce reports.…”
Section: Enablersmentioning
confidence: 99%
See 1 more Smart Citation
“…21,31,32 Pellicer 33 reported that both the standardization of a control management process and the implementation of "best practice" project control enhance the effectiveness of PCS by reducing the effort required to collect and enter data and produce reports.…”
Section: Enablersmentioning
confidence: 99%
“…From a system perspective, a successful implementation strategy is one that encompasses information technology, training in the utilization of computer software and procedures, definition of the requirements for a PCS, and the development of PCS guidance and work instructions. 21,31,32 Pellicer 33 reported that both the standardization of a control management process and the implementation of "best practice" project control enhance the effectiveness of PCS by reducing the effort required to collect and enter data and produce reports.…”
Section: Enablersmentioning
confidence: 99%